Waste less time on Facebook — follow Brilliant.
×

GCD property

Note by Shivamani Patil
2 years, 10 months ago

No vote yet
1 vote

Comments

Sort by:

Top Newest

\(c | (a+b) \rightarrow c|a \wedge c|b\) is wrong. Easily counterexample as \(a = 4, b = 5, c = 3)\).

Samuraiwarm Tsunayoshi - 2 years, 10 months ago

Log in to reply

Hint: use Bezout's identity

Samuraiwarm Tsunayoshi - 2 years, 10 months ago

Log in to reply

Another hint: \((a,b) = 1\) if and only if \(ax+by = 1\).

Samuraiwarm Tsunayoshi - 2 years, 10 months ago

Log in to reply

@Samuraiwarm Tsunayoshi Hey,@Samuraiwarm Tsunayoshi check my sol in Kartik Sharma's solution's replay box.

Shivamani Patil - 2 years, 10 months ago

Log in to reply

Let \(a = {{p}_{1}}^{{e}_{1}}{{p}_{2}}^{{e}_{2}}{{p}_{3}}^{{e}_{3}}..... {{p}_{n}}^{{e}_{n}}\)

Now, \(a = 0 mod {p}_{i}\)

We know that gcd(a,b) = 1, so none of the \({p}_{i}\) divide b

\(cn = a + b\)

\(cn mod {p}_{1} = 0 + x\)

\(cn = x mod {p}_{1}\)

And so on, till \({p}_{n}\) which tells us that \({p}_{i}\) doesn't divide c. Therefore there is no common divisor of c and a, so, \(gcd(a,c) = 1\)

Similarly we can show for b.

@shivamani patil Check out and now I think it is fine.

Kartik Sharma - 2 years, 10 months ago

Log in to reply

If gcd(a,b) then \(ax+by=1\) also \(cn=a+b\) for some \(n\) because \(c|a+b\).Therefore \(cn-b=a\),substituting \(cn-b=a\) in first equation we get \(x(cn-b)+by=1=cnx-bx+by=c(nx)+b(y-x)\) which implies gcd(c,b)=1.Similarly gcd(c,a)=1.@Kartik Sharma how is it??Your's is good.

Shivamani Patil - 2 years, 10 months ago

Log in to reply

I knew about this method too but that is already discussed by Samuraiwarm Tsunayoshi.

Kartik Sharma - 2 years, 10 months ago

Log in to reply

@Kartik Sharma But I solved it independently @Kartik Sharma

Shivamani Patil - 2 years, 10 months ago

Log in to reply

Yep, looks good.

Samuraiwarm Tsunayoshi - 2 years, 10 months ago

Log in to reply

Note that \( a|b \) implies that there exists an integer \( k \) suck that \( ka = b \), not \( kb = a \). So your assumption that \( c = n(a+b) \) is wrong. It should be \( cn = a+b \).

Siddhartha Srivastava - 2 years, 10 months ago

Log in to reply

Oh damn yes ! I knew it but just a silly mistake. Now, I am gonna edit it.

Kartik Sharma - 2 years, 10 months ago

Log in to reply

@Kartik Sharma Looking forward to your solution!

Samuraiwarm Tsunayoshi - 2 years, 10 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...